The Role of Tyrosine Kinases as a Critical Prognostic Parameter and Its Targeted Therapies in Ewing Sarcoma - Jin, Wook (Frontiers in Cell and Developmental Biology, 2020)
Ewing sarcoma (ES) is a rare, highly aggressive, bone, or soft tissue-associated tumor. Although this sarcoma often responds well to initial chemotherapy, 40% of the patients develop a lethal recurrence of the disease, with death recorded in 75–80% of patients with metastatic ES within 5 years, despite receiving high-dose chemotherapy. ES is genetically well-characterized, as indicated by the EWS-FLI1 fusion protein encoded as a result of chromosomal translocation in 80–90% of patients with ES, as well as in ES-related cancer cell lines. Recently, tyrosine kinases have been identified in the pathogenesis of ES. These tyrosine kinases, acting as oncoproteins, are associated with the clinical pathogenesis, metastasis, acquisition of self-renewal traits, and chemoresistance of ES, through the activation of various intracellular signaling pathways. This review describes the recent progress related to cellular and molecular functional roles of tyrosine kinases in the progression of ES.